2003
DOI: 10.1046/j.1365-2761.2003.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic gill disease: sequential pathology in cultured Atlantic salmon, Salmo salar L.

Abstract: Amoebic gill disease (AGD) affects the marine culture phase of Atlantic salmon, Salmo salar L., in Tasmania. Here, we describe histopathological observations of AGD from smolts, sampled weekly, following transfer to estuarine/marine sites. AGD was initially detected histologically at week 13 post-transfer while gross signs were not observed for a further week post-transfer. Significant increases (P < 0.001) in the proportion of affected gill filaments occurred at weeks 18 and 19 post-transfer coinciding with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
145
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 43 publications
19
145
1
1
Order By: Relevance
“…can infect gills and cause AGD in salmonids (Group 1) after KMnO 4 disinfection and with very low levels of culturable bacteria. Therefore, in agreement with other authors we have shown that the amoeba can be a primary pathogen and cause AGD in salmon (Kent et al 1988, Roubal et al 1989, Munday et al 1990, Dyková et al 1995, Adams & Nowak 2003. …”
supporting
confidence: 92%
“…can infect gills and cause AGD in salmonids (Group 1) after KMnO 4 disinfection and with very low levels of culturable bacteria. Therefore, in agreement with other authors we have shown that the amoeba can be a primary pathogen and cause AGD in salmon (Kent et al 1988, Roubal et al 1989, Munday et al 1990, Dyková et al 1995, Adams & Nowak 2003. …”
supporting
confidence: 92%
“…Fish returned to a similar level of infection 8 wk post-bath. Also, Adams & Nowak (2003) found AGD-affected fish from a commercial salmon farm to have 10 to 20% of gill filaments with an AGD lesion 18 wk after first being introduced to estuarine/ marine sites from freshwater. Differences in infection rates between laboratory and field situations occur due to optimal conditions for AGD in the laboratory, where no freshwater bathing treatment is administered, and there is the potential for continuous infection of gills under laboratory conditions because water is recirculated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mucus production, via significant elevations in mucous cell numbers, has also been noted in association with AGD (Munday et al 1990, Nowak & Munday 1994, Adams & Nowak 2003, Roberts & Powell 2003, and, although gill mucus production does not appear to greatly influence O 2 uptake in rainbow trout exposed to a chemical gill irritant, there is evidence to suggest that it does impair CO 2 excretion (Powell & Perry 1996, 1997, 1999, and this could lead to an acute acid -base disturbance. Although caudal blood pH was significantly elevated in Series II fish by Day 2, it appeared to fall from Day 7 onwards and consistently decreased over the remainder of the sampling period.…”
Section: Discussionmentioning
confidence: 95%
“…The actual effect of AGD lesions on gill blood flow is not currently understood; however, pathological studies of AGD have shown that amoeba presence and attachment to gill filaments initially results in hyperplasia of epithelial cells (Adams & Nowak 2003). Epithelial cells play a prominent role in respiratory gas transfer (Lin & Randall 1995); thus, any alterations in epithelial thickness can potentially decrease functional surface area for transfer of respiratory gases.…”
Section: Discussionmentioning
confidence: 99%